Gastric metastasis and peritoneal carcinosis revealing primary breast cancer: an unusual presentation - Shema Ayadi; Souhir Monastiri; Amine Ben Safta; Mehdi Hammami; Imen Samaali; Mehdi Kammoun; Ahlem Blel; Raoudha Aloui; Yosra Zaimi; Leila Mouelhi (Future Science OA, 2024)
Breast cancer is the most frequent cancer among women. Gastrointestinal tract metastases are uncommon and might be misidentified as primary carcinoma.A noteworthy case-study involved 53-year-old-woman complaining from epigastric pain, ascites and overall health decline. Initial investigations were inconclusive, prompting laparoscopic peritoneal biopsies which revealed independent cell proliferation. Subsequently, a second look upper digestive endoscopy showed multiple gastric ulcerations suggestive of gastric carcinoma. Histologic examination confirmed independent cell proliferation with estrogen receptors expression, a characteristic feature of breast carcinoma. Further investigations led to bilateral invasive lobular breast carcinoma diagnosis. Epirubicin cycophosphamide was prescribed after progression under letrozole ribocilib therapy.This case aims to raise awareness among clinicians about the importance of ruling out breast cancer in patients with peritoneal carcinosis and paying attention to digestive symptoms in breast cancer patients with careful gastric endoscopic examination to avoid misdiagnosis.